Robust sensorless Control Of BLDC motor using Second derivative Function of the Sum of terminal Voltages, ISSN 1451-4869 - Boughaba Abdelali; Chaabane Mabrouk; Benaggoune Said (Serbian Journal of Electrical Engineering, 2012)
This paper proposes a new sensorless control method for the speed and position control of a BLDC Motor. This sensorless drive technique calculates the commutations instants (duration of commutation) by deriving the sum of the terminal voltages of the motor (SigVi). Thus, it is possible to estimate the rotor position (and back EMF of the motor) by only using measurements of the stator line currents and voltages. The implantation of these detectors is easy and cheap. This method is quite robust across variations in stator resistance due to changes in temperature or frequency. With this method the motor can be started without needing the initial position of the rotor. This proposed method is validated through extensive simulations at different speeds, and a very satisfactory performance has been achieved.